Hair cell damage recruited Lgr5-expressing cells are hair cell progenitors in neonatal mouse utricle - Lin, Jinchao; Zhang, Xiaodong; Wu, Fengfang; Lin, Weinian (Frontiers in Cellular Neuroscience, 2015)
Damage-activated stem/progenitor cells play important roles in regenerating lost cells and in tissue repair. Previous studies reported that the mouse utricle has limited hair cell regeneration ability after hair cell ablation. However, the potential progenitor cell population regenerating new hair cells remains undiscovered. In this study, we first found that Lgr5, a Wnt target gene that is not usually expressed in the neonatal mouse utricle, can be activated by 24 hour neomycin treatment in a sub-population of supporting cells in the striolar region of the neonatal mouse utricle. Lineage tracing demonstrated that these Lgr5-positive supporting cells could regenerate new hair cells in explant culture. We isolated the damage-activated Lgr5-positive cells with flow cytometry and found that these Lgr5-positive supporting cells could regenerate hair cells in vitro, and self-renew to form spheres, which maintained the capacity to differentiate into hair cells over seven generations of passages. Our results suggest that damage-activated Lgr5-positive supporting cells act as hair cell progenitors in the neonatal mouse utricle, which may help to uncover a potential route to regenerate hair cell in mammals.